ANALYSIS OF PSYCHO-SOCIAL RISK FACTORS IN PATIENTS WITH RECENT ACUTE CORONARY SYNDROME: A CASE-CONTROL STUDY - Gupta, Gaurav; Sinha, Santosh Kumar; Thakur, Ramesh; Jha, Mukesh Jitendra; KRISHNA, VINAY; Goel, Amit; Kumar, Ashutosh; Mishra, Vikas; SACHAN, MOHIT; VARMA, CHANDRA MOHAN; et al. (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: Although psycho-social factors are reported to be independently associated with myocardial ischemia in many studies, the majority of these were done in the western population. This was conducted in India to determine the impact of psycho-social factors in subjects with the recent acute coronary syndrome (ACS). Methods: Patients with the first episode of ACS within 4 weeks of onset at LPS Institute of Cardiology, Kanpur, India between 2013 and 2015 were enrolled as cases. Control was community-based individuals without coronary artery disease. Both were compared for demographic variables, the psycho-social profile including annual income, education status, depression, stressful life events (using presumptive stressful life events scale, i.e. PSLES), and independent predictors were determined using multiple logistic regression analysis and were computed as odds ratio (OR). Results: Between 200 cases and 200 controls, respectively, statistically significant difference was observed in mean annual income (2.74±1.95 vs. 2.23±1.22 lac rupees; p<0.05), smoking exposure (13.93±16.17 vs. 4.88±3.10 pack years; p<0.05), mean number of stressful life events (8.18±2.57 vs. 4.14±1.63; p<0.05). Depression (48% vs. 27%; p<0.05) while education status was comparable. Further, odds of having myocardial infarction were higher for subjects with mild-to-moderate depression (OR: 2.45), family history of heart disease (OR: 2.25), hypertensive males (OR: 1.43), and diabetic females (OR: 1.22). Conclusion: Psycho-social factors, particularly depression may have a significant role in the prognosis of ACS. Further systematic studies are warranted to provide more important insights regarding the magnitude of the association between psycho-social factors and the onset of ACS. Keywords: Coronary artery disease, Depression, Psycho-social factors, Presumptive stressful life events scale, Stressful life events.